1990
DOI: 10.1080/07315724.1990.10720349
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium bioavailability from magnesium citrate and magnesium oxide.

Abstract: This study compared magnesium oxide and magnesium citrate with respect to in vitro solubility and in vivo gastrointestinal absorbability. The solubility of 25 mmol magnesium citrate and magnesium oxide was examined in vitro in solutions containing varying amounts of hydrochloric acid (0-24.2 mEq) in 300 ml distilled water intended to mimic achlorhydric to peak acid secretory states. Magnesium oxide was virtually insoluble in water and only 43% soluble in simulated peak acid secretion (24.2 mEq hydrochloric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 15 publications
1
55
1
4
Order By: Relevance
“…Our results suggest that high urinary magnesium can increase calciuria and potentially increase stone risk. Some have espoused the notion that magnesium is efficacious in preventing stone formation by binding or complexing oxalate in the bowel and urine, 26,27,40,41 by inhibiting calcium oxalate crystal formation, 26,42,43 and by increasing urinary citrate when given as alkali salt. 44 In vitro studies have shown that magnesium is an inhibitor of calcium oxalate crystal growth in artificial, rodent, and human urine but at supraphysiologic concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that high urinary magnesium can increase calciuria and potentially increase stone risk. Some have espoused the notion that magnesium is efficacious in preventing stone formation by binding or complexing oxalate in the bowel and urine, 26,27,40,41 by inhibiting calcium oxalate crystal formation, 26,42,43 and by increasing urinary citrate when given as alkali salt. 44 In vitro studies have shown that magnesium is an inhibitor of calcium oxalate crystal growth in artificial, rodent, and human urine but at supraphysiologic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the remaining 11 trials, only the test potassium or magnesium salts were given. 27,31 Forty-seven individuals participated in the four trials (four to 21 per trial). In group 2, KHCO 3 was given in one trial, 33 and K 3 Citrate was given in seven trials.…”
Section: Human Data Analysismentioning
confidence: 99%
“…Mg oxide has a lower bioavailability than citrate (Lindberg et al 1990) or Mg-L-aspartate-HC1 (Muhlbauer et al 1991). There are no significant differences between Mg lactate, citrate and hydroxide (Bohmer et al 1990) but Mg orotate has a higher bioavailability than Mg hydroxycarbonate (Schlebusch et al 1992).…”
Section: F a C T O R S A F F E C T I N G B I O A V A I L A B I L I T Ymentioning
confidence: 99%
“…The Mg/creatinine ratio reveals to possible bias due to incomplete urine collection. Furthermore, a normal urinary Mg/creatinine ratio indicates normal urinary Mg excretion and adequate Mg intake [28,29]. Our finding of normal Mg/creatinine ratios implies that there was complete urine collection and adequate Mg intake for all subjects.…”
Section: Discussionmentioning
confidence: 80%